Puentes teatrales, montajes “de ida y vuelta”: argentinos a la conquista de la escena barcelonesa - Sharon G. Feldman (Les Cahiers ALHIM)
Throughout the present decade, a succession of playwrights, directors and theatre artists from Argentina have gone about leaving their imprint upon the Barcelona theatrical landscape (and by extension, that of Catalunya), an artistically fertile ground that, since the 1980s (and since the period of the democratic transition), has exhibited an undeniable yearning to breathe fresh air, to imbue itself with new aesthetic paradigms and become an essential point of reference within the world of European drama. Today Barcelona finds itself immersed in the most dynamic and extraordinary period in its modern theatre history, with an abundant outpouring of new drama and new theatre spaces. The Argentine contributions to the current period are without question, visible in stagings, workshops and coproductions, in addition to certain thematic and structural inclinations. I shall trace here the marks left by some of the most prominent Argentine names upon the Barcelona theatre scene and highlight some of the signs that confirm their impact.